2018
DOI: 10.1038/s41598-018-28404-y
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of chemokine CXCL10 enhances chronic pulmonary inflammation in tree shrew collagen-induced arthritis

Abstract: Chronic pulmonary inflammation (CPI) gives rise to serious lung injuries in rheumatoid arthritis (RA) patients. However, the molecular mechanism underlying the pathogenesis of RA-associated CPI remains little understood. Here we established a novel tree shrew-based collagen-induced arthritis (TsCIA) model to study RA-associated CPI. Our results showed that typical CPI but not fibrosis developed pathologically in the TsCIA model. Furthermore, abnormal up-regulation of pulmonary chemokine CXCL10 was directly ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 46 publications
(53 reference statements)
0
14
0
Order By: Relevance
“…The CXCL10 and CXCL9 genes encode for chemotactic agents for T-lymphocytes and monocytes and can bind to CXCR3, which may facilitate the proliferation, angiogenic activity, and survival of human mesangial cells within a heterotrimeric G-protein signaling pathway. Gao et al showed that inhibition of CXCR3 (a CXCL10 receptor) significantly reduced chronic pulmonary inflammation by reducing inflammatory cell recruitment [32]. Studies have also reported that CXCL10 is necessary for cancer cell growth [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…The CXCL10 and CXCL9 genes encode for chemotactic agents for T-lymphocytes and monocytes and can bind to CXCR3, which may facilitate the proliferation, angiogenic activity, and survival of human mesangial cells within a heterotrimeric G-protein signaling pathway. Gao et al showed that inhibition of CXCR3 (a CXCL10 receptor) significantly reduced chronic pulmonary inflammation by reducing inflammatory cell recruitment [32]. Studies have also reported that CXCL10 is necessary for cancer cell growth [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…no. ab123104; monoclonal; raised in rabbit; 1:40 dilution; Abcam) was performed as previously described (13).…”
Section: Methodsmentioning
confidence: 99%
“…Hub genes CXCL10 in module 2 and EHHADH in module 6 were shown to be respectively regulated by hsa-miR-411-3p and hsa-miR-487a, being involved in inflammatory and amino acid metabolism pathways for HASC differentiation. As reported for LEP above, inflammation promotes the adipocyte differentiation of HASCs, whereas CXCL10 is a well-known pro-inflammatory chemokine (47). Therefore, CXCL10 may be upregulated in adipocyte differentiated HASCs, which was confirmed in the present study.…”
Section: Discussionmentioning
confidence: 81%